MEMS transducers low-cost fabrication using SU-8 in a sacrificial layer-free process. (21st February 2017) - Ge, Chang; Cretu, Edmond
Abstract: We report novel low-cost and rapid fabrication technologies for the fabrication of movable polymer-based MEMS structures, electrically actuated. Using SU-8 photoresist as structural material, both ordinary and functionalized by conductive fillers (nano-Ag particles and carbon nanotubes), the novel fabrication methods provide simple processes, without the use of any sacrificial layer, for achieving suspended structures (beams and membranes) through either binary or gray-scale photolithography. Experimental validation has demonstrated high yields (over 99% for one of the process flows) in achieving electrostatically actuated microstructures with resonant frequencies in the 0.5–0.8 MHz range, with a stable dynamic behavior tested for a period longer than three months. The technology also confirms that 'doping' SU-8 with conductive fillers can preserve its photo-patterning capabilities, while modifying other physical properties (electrical conductivity). As the patterning of SU-8 films can take place on either rigid or flexible substrates, this low-cost technology promises a wide range of applications.